ETNOBOTANI TUMBUHAN BERGUNA PADA MASYARAKAT DESA LEGOKHERANG KECAMATAN CILEBAK KABUPATEN KUNINGAN - Khairunisa Amalia; Ai Nurlaila; Yayan Hendrayana (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
Legokherang Village is an agrarian village so that agriculture, livestock and plantations develop well. Besides that, there are still traditional cultures such as Sidekah Bumi and Pesta Dadung that take advantage of agricultural products and plants from their environment. It is important to document the ethnobotany knowledge of the Legokherang Village community to determine the use of plants, the parts of plants used and how to process them so that the community's knowledge in the use of plants is not lost. Research on ethnobotany of useful plants in Legokherang Village was carried out by survey methods and semi- structured interviews or questionnaires with the determination of respondents based on the snow ball sampling technique.. The results showed that the number of species obtained from ethnobotany were 125 species and 53 plant families. Food-producing plants and medicinal plants were mostly used, namely 39 species and 31 species. The most useful part of the plant is the leaves, for plant processing it is done in several ways, namely burning, boiling, pounding, slicing and using it directly without processing.Keywords: ethnobotany, useful plants